Remdesivir, mAb114, REGN-EB3, and ZMapp partially rescue nonhuman primates infected with a low passage Kikwit variant of Ebola virus - Prasad, Abhishek N.; Woolsey, Courtney; Borisevich, Viktoriya; Agans, Krystle N.; Deer, Daniel J.; Geisbert, Joan B.; Harrison, Mack B.; Dobias, Natalie S.; Fenton, Karla A.; Cross, Robert W.; Geisbert, Thomas W. (Nature communications, 2025)
In 2018, a clinical trial of four investigational therapies for Ebola virus disease (EVD), known as the PALM trial, was conducted in the Democratic Republic of Congo. All patients received either the antiviral remdesivir (RDV) or a monoclonal antibody product: ZMapp, mAb114 (Ebanga), or REGN-EB3 (Inmazeb). The study concluded that both mAb114 and REGN-EB3 were superior to ZMapp and RDV in reducing mortality from EVD. However, the data suggested that some patients in the RDV and ZMapp groups might have been sicker at the time of treatment initiation. Here, we assessed the efficacy of each of these therapies in a uniformly lethal rhesus monkey model of EVD when treatment was initiated 5 days after Ebola exposure. Treatment with RDV, mAb114, REGN-EB3, and ZMapp each resulted in similar survival (approximately 40%). Survival was associated with circulating viral load at treatment initiation. A trend of more escape mutants in the GP1 and GP2 domains was observed for the mAb114 group. Our data show similar suboptimal efficacy of individual therapeutics in the uniformly lethal NHP model of EVD, supporting further clinical investigation of therapeutic combinations to maximize the overall therapeutic effect and improve patient outcomes, particularly for the treatment of advanced stage EVD. Prasad et al. assess four therapeutics in preventing lethal disease in an established nonhuman primate model of Ebola virus infection. They find that each therapy results in ~ 40% survival, suggesting the use of alternative strategies, such as combining therapeutics to combat Ebola.